Revealing the inner worlds of young children : the MacArthur story stem battery and parent-child narratives - Emde, Robert N.; Wolf, Dennie; Oppenheim, David, 1958- (Oxford ; New York : Oxford University Press, 2003)
Typically, we make sense of our experiences and interactions in a way that is guided by emotion and that takes the form of a narrative or a story. Using narratives, we can tell others about our experience, share common meanings, imagine possibilities, and co-construct new meanings. It is thus a momentous development when, at around age three, a child acquires the capacity to construct narratives. The book reports the work of a 20-year collaboration between 36 psychologists who have created and investigated a new tool to elicit and analyze children's narratives. This tool is the MacArthur Story Stem Battery, a systematic collection of story beginnings that are referred to as 'stems.' These stems are designed to elicit information from children about their representational worlds. This method is particularly exciting because using it allows developmental psychologists to gain information directly from children about their emotional states and what they are able to understand, and in turn, to use this information to explore significant emotional differences among children.
Early narratives : a window to the child's inner world / Robert N. Emde -- Narratives of emotional experince : their nature and development / Dennis Palmer Wolf -- The MacArthur story stem battery : development, administration, reliability, validity and reflections about meaning / Inge Bretherton and David Oppenheim -- The MacArthur narrative coding system : one approach to highlighting affective meaning-making in the MacArthur story stem battery / Joann L. Robinson and Linda Mantz-Simmons -- Narrative emotion coding system / Susan L. Warren -- The structure of five-year- old children's play narratives within the MacArthur story stem methodology / Kai von Klitzing, Kim Kelsay, and Robert N. Emde -- Temperament and guilt representations in children's narratives / Nazan Aksan and H.H. Goldsmith -- Children's emotional resolution of mssb narratives : relations with child behavior problems and parental psychological distress / David Oppenheim -- An attachment perspective on children's emotion narratives : links across generations / Miriam Steele [and others] -- Emotional apprenticeships : the development of affect regulation during the pre-school years / Eva Appelman and Dennie Palmer Wolf -- Portrayals in maltreated children's play narratives : representations or emotion regulation? / Robert B. Clyman -- Narratives in risk and clinical populations / Susan L. Warren -- Mental representations and defences in severely maltreated children : a story stem battery and rating system for clinical assessment and research applications / Jill Hodges [and others] -- The mother-child co-construction of an event lived by the preschool child : the role of the mother's knowledge of "what happened" / Christine Gertsch Bettens, Nicolas Favez, and Daniel N. Stern -- Patterns of maternal affect regulation during the co-construction of preschoolers autobiographical narratives / Nicolas Favez -- Relationships and interactions of mothers and metaplot with three-year-old kibbutz children in two functional contexts / R. Landau, Y. Eshel V. Kipnis, and M. ben-Aaron -- Dialogues of seven-year-olds with their mothers about emotional events : development of a typology / Nina Koren-Karie -- Affective meaning making among young peers in narrative co-constructions / Ora Aviezer.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Storytelling ability in children; Cognition in children; Children -- Language; Preschool children; Cognition; Emotions; Narrative medicine; Child psychology; Verbal behavior; Children; Child Language; Child, Preschool; Cognition; Emotions; Interview, Psychological; Narration; Psychology, Child; Verbal Behavior; Child; Art de conter chez l'enfant.; Cognition chez l'enfant.; Enfants -- Langage; Enfants d'âge préscolaire.; Cognition; Émotions.; Médecine narrative; Enfants -- Psychologie; Comportement verbal; Enfants; Enfance; cognition; emotion; children (people by age group); childhood; PSYCHOLOGY -- Developmental -- Child; PSYCHOLOGY -- Psychotherapy -- Child & Adolescent; FAMILY & RELATIONSHIPS -- Child Development; Verbal behavior; Preschool children; Narrative medicine; Emotions; Cognition; Children; Child psychology; Children -- Language; Cognition in children; Storytelling ability in children; Education; Electronic books